Visualization of Fluoride Ions In Vivo Using a Gadolinium(III)-Coumarin Complex-Based Fluorescence/MRI Dual-Modal Probe - Yue Wang; Renfeng Song; Huan Feng; Ke Guo; Qingtao Meng; Haijun Chi; Run Zhang; Zhiqiang Zhang (Sensors, 2016)
A new Gadolinium(III)–coumarin complex, DO3A-Gd-CA, was designed and prepared as a dual-modal probe for simultaneous fluorescence and relaxivity responses to fluoride ions (F−) in aqueous media and mice. DO3A-Gd-CA was designed by using Gd(III) center as an MRI signal output unit and fluoride binding site, and the 4-(diethylamino)-coumarin-3-carboxylic acid (CA) as a fluorescence reporter. Upon the addition of fluoride ions to the solution of DO3A-Gd-CA, the liberation of the coordinated CA ligand led to a 5.7-fold fluorescence enhancement and a 75% increase in the longitudinal relaxivity (r1). The fluorescent detection limit for fluoride ions was determined to be 8 μM based on a 3σ/slope. The desirable features of the proposed DO3A-Gd-CA, such as high sensitivity and specificity, reliability at physiological pH and low cytotoxicity enable its application in visualization of fluoride ion in mice. The successful in vivo imaging indicates that DO3A-Gd-CA could be potentially used in biomedical diagnosis fields.